The Role of Traffic Patrol in Preventing Two-Wheel Traffic Violations at Ngawi Police - Nooryono, Makhsyar (Police Studies Review, 2024)
The presence of the National Police for the community in the traffic sector is closely related to the aim of ensuring security, safety, order and smooth traffic flow, which can only be achieved through collaborative efforts of the community and the traffic police. The problems that will be studied in this research can be described as follows: 1) What is the role of patrols through direct patrols towards the community to prevent traffic violations in the Ngawi Police jurisdiction?, 2) What factors influence the implementation of direct patrols towards the community to prevent traffic violations traffic in the jurisdiction of the Ngawi police station? This research uses a qualitative approach. The type of research used is descriptive analytical. The results of the research show that the Turjawali Unit of the Ngawi Police Traffic Unit has an important role in preventing and minimizing traffic violations through traffic patrols in the jurisdiction of the Ngawi Police. The factors that influence the implementation of direct patrols towards the community to prevent traffic violations in the jurisdiction of the Ngawi Police are the inadequate resources of the National Police personnel qualitatively and quantitatively, the budget is still limited, the facilities and infrastructure are minimal, the awareness and discipline of the community is still low. low.